Etiología del "amachamiento" del frijol común en Costa Rica - Morales, Francisco José; Araya Fernández, CM; Hernández, J.C.; Arroyave, José A.; Cuervo Ibáñez, Maritza; Velasco, Ana Cecilia; Castaño J., Mauricio (1999)
Etiology of "amachamiento" "(sterility") in Phaseolus vulgaris in Costa Rica. In the last decade the problem known as "amachamiento" ("sterility") has been increasing in the main bean production regions of Costa Rica. This problem consists of a reduction of 24% - 50% in the production of affected bean varieties, without the plants showing severe symptoms. An analysis of bean plants of improved varieties, with symptoms of "amachamiento", revealed the presence of an isometric virus. Some bean plants of local varieties contained the isometric virus and a potyvirus identified as the common mosaic virus (BCMV). The isometric virus was characterized by electron microscopy, serology, electrophoresis and nucleic acid analyses, as a strain, adapted to bean, of the cowpea clorotic mottle bromovirus (CCMV). This virus had already been reported in Costa Rica in 1972, as the causal agent of bean "yellow stipple", but had not been associated with the symptoms of "amachamiento". The characteristic symptoms of "amachamiento" were reproduced in this investigation with CCMV. This virus is transmitted mechanically and by chrysomelid beetles, but not by seed. An integrated management program is being implemented for CCMV and its insect vectors in Costa Rica.